Arbitrage pricing theory (APT) e variáveis macroeconômicas - Adriana Schor; Marco Bonomo; Pedro L. Valls Pereira (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1998)
This paper analyses monthly returns of 10 share portfolios negotiated at Bovespa between 1987 and 1997 in order to test the APT model. Macroeconomic factors were created as sources of common variance of these assets. The factors were statistically significant in explaining the relationship between the asset returns in general; besides, evidence was found in favor of the APT.
Keywords: 330